Solve for u 2u+9-6u=19

Math
2u+9-6u=19
Subtract 6u from 2u.
-4u+9=19
Move all terms not containing u to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
-4u=19-9
Subtract 9 from 19.
-4u=10
-4u=10
Divide each term by -4 and simplify.
Tap for more steps…
Divide each term in -4u=10 by -4.
-4u-4=10-4
Cancel the common factor of -4.
Tap for more steps…
Cancel the common factor.
-4u-4=10-4
Divide u by 1.
u=10-4
u=10-4
Simplify 10-4.
Tap for more steps…
Cancel the common factor of 10 and -4.
Tap for more steps…
Factor 2 out of 10.
u=2(5)-4
Cancel the common factors.
Tap for more steps…
Factor 2 out of -4.
u=2⋅52⋅-2
Cancel the common factor.
u=2⋅52⋅-2
Rewrite the expression.
u=5-2
u=5-2
u=5-2
Move the negative in front of the fraction.
u=-52
u=-52
u=-52
The result can be shown in multiple forms.
Exact Form:
u=-52
Decimal Form:
u=-2.5
Mixed Number Form:
u=-212
Solve for u 2u+9-6u=19

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top